2018
DOI: 10.1097/sle.0000000000000563
|View full text |Cite
|
Sign up to set email alerts
|

What is the Appropriate Nodular Diameter in Thyroid Cancer for Extraction by Transoral Endoscopic Thyroidectomy Vestibular Approach Without Breaking the Specimens? A Surgicopathologic Study

Abstract: Transoral Endoscopic Thyroidectomy Vestibular Approach (TOETVA) is a novel technique with better cosmetic results. However, extraction of a large malignant thyroid nodule from the central incision of TOETVA necessitates breaking it into pieces to avoid mental nerve injury, a situation that may violate a proper oncological surgery. In this study, we sought the appropriate nodular diameter in thyroid cancer to be removed in an intact status through the central incision of the TOETVA technique. A total of 27 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 20 publications
0
21
0
2
Order By: Relevance
“…Taking into consideration the limitations of TOETVA and the natural history of differentiated thyroid cancer, Wu et al (47) reported that this natural orifice transluminal endoscopic approach can be safely performed in case of low-risk thyroid carcinoma up to 2 cm in diameter with adequate oncologic outcomes. Similarly, Anuwong et al (48) did not consider patients with thyroid malignant tumors larger than 2 cm candidates for TOETVA because it is crucial to extract the tumor intact, and it cannot be morselized as is done with benign nodules.…”
Section: Transoral Endoscopic Thyroidectomy With Vestibular Approach (Toetva)mentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into consideration the limitations of TOETVA and the natural history of differentiated thyroid cancer, Wu et al (47) reported that this natural orifice transluminal endoscopic approach can be safely performed in case of low-risk thyroid carcinoma up to 2 cm in diameter with adequate oncologic outcomes. Similarly, Anuwong et al (48) did not consider patients with thyroid malignant tumors larger than 2 cm candidates for TOETVA because it is crucial to extract the tumor intact, and it cannot be morselized as is done with benign nodules.…”
Section: Transoral Endoscopic Thyroidectomy With Vestibular Approach (Toetva)mentioning
confidence: 99%
“…Taking into consideration the limitations of TOETVA and the natural history of differentiated thyroid cancer, Wu et al. ( 47 ) reported that this natural orifice transluminal endoscopic approach can be safely performed in case of low-risk thyroid carcinoma up to 2 cm in diameter with adequate oncologic outcomes. Similarly, Anuwong et al.…”
Section: Transoral Endoscopic Thyroidectomy With Vestibular Approach (Toetva)mentioning
confidence: 99%
“…Finally, we would like to highlight that the literature also states the TOETVA and TOETRA techniques cannot be considered for all patients. The exclusion criteria include thyroid gland with high volume, tumor staging, presence of previous treatments, and patient anthropometrics (7)(8)(9)(10). The defenders of the procedure consider TOETVA and TOETRA to be minimally invasive.…”
Section: Financial and Social Burdensmentioning
confidence: 99%
“…Publications advocating TOETVA (or TOETRA) present clear data of feasibility and remarkable aesthetic results. Some publications demonstrate similar (incipient) oncological results when compared to the classic procedure (7)(8)(9)(10).…”
mentioning
confidence: 92%
“…Fine needle aspiration cytologically benign and indeterminant nodules ≤ 6 cm and a thyroid lobe with a maximum dimension ≤ 10 cm meet the recommended inclusion criteria [33]. Select patients with T1 well-differentiated thyroid carcinoma can also be considered; however, such patients are not recommended as part of a candidate surgeon’s initial cohort [22, 34]. In a similar fashion, candidate surgeons may also wish to begin their transoral vestibular experience with lobectomies exclusively, as they gain familiarity with the approach [30].…”
Section: Candidacy–patientsmentioning
confidence: 99%